Saglik Çalisanlarinda Örgütsel Adalet Üzerine Yazilmis Lisansüstü Tezlerin Bibliyometrik Yöntemle Incelenmesi - Korkmazer, Fuat; Pirol, Mahfure (Ibrahim APAK, 2021)
Bu çalismada saglik çalisanlarinda örgütsel adalet konulu lisansüstü tezlerin bibliyometrik analiz yöntemi ile incelenmesi amaçlanmaktadir. Konu ile ilgili tez çalismalarinin son 20 yilda daha yogun yazilmaya baslandigi tespit edilmistir. Bu sebeple 2000-2020 yillari araligi seçilerek bu aralikta üretilmis olan yüksek lisans ve doktora tezleri tezlerin yayinlandigi yillar, tezlerin türleri, tez danismanlarinin unvanlari, tezlerin üniversitelere göre dagilimi, tezlerin enstitülere göre dagilimi, tezlerin anabilim dallarina göre dagilimi, tezlerin arastirma yöntemine göre dagilimi,  örgütsel adaletin birlikte çalisildigi konulara göre dagilim gibi göstergeler kullanilarak bibliyometrik yöntemle analiz edilmistir. Analiz sonucunda YÖK (Yüksekögretim Kurulu) veri tabaninda 52’si yüksek lisans 8’i doktora olmak üzere toplam 60 teze ulasilmistir. Arastirma sonucunda en çok tezin kamu üniversiteleri olan Marmara Üniversitesi ile Sivas Cumhuriyet Üniversitesinde çalisildigi görülmüstür. Çalisma sonucunda saglik çalisanlarinda örgütsel adalet konulu ilk tez çalismasinin 2007 yilinda yazildigi tespit edilmistir. Örgütsel adalet ile çalisilan konular incelendiginde ise ilk sirada örgütsel baglilik konusunun yer aldigi görülmüstür.

In this study, it is aimed to examine postgraduate theses on organizational justice in healthcare professionals by using bibliometric analysis method. It has been determined that thesis studies on the subject have been written more intensely in the last 20 years. For this reason, graduate and doctoral theses produced in this range from 2000-2020, the years of publication of theses, types of theses, titles of thesis supervisors, distribution of theses by universities, distribution of theses by institutes, distribution of theses by departments, distribution of theses by research method, The organizational justice has been analyzed by bibliometric method using indicators such as the distribution according to the subjects that are studied together. As a result of the analysis, YÖK (Council of Higher Education) database, a total of 60 theses, 52 of which are master's, 8 of which are doctorate have been reached. As a result of the research, it was seen that the thesis was mostly studied in public universities, Marmara University and Sivas Cumhuriyet University. As a result of the study, it was determined that the first thesis on organizational justice in healthcare workers was written in 2007. When the topics dealt with with organizational justice are examined, it is seen that organizational commitment takes the first place.
A Bibliometric Investigation of Graduate thesis on Organizational Justice in Healthcare Professionals
Keywords: Business Administration; Isletme